Causes And Consequences Of Child Labour Abuse In South West Shoa: The Case Of Wonchi District, Wonchi - Dereje Tamene (My University, 2016)
This study aims at assessing child labour abuse at Wonchi district of South West Shoa Zone. The study looks at the factors for the involvement of children in the exploitative works; the living and working conditions of child labourers; the impacts of child labour on the working children; the perceptions of child labour from the perspectives of working children, employers and members of the society and the challenges and abusive practices child labourers face. To undertake this study the researcher employed qualitative research method as the sole technique of data collection. The researcher gathered information pertinent to the study through structured and unstructured interviews, observation, case study and focus group discussion. Theories of child labour such as the ‘labour market’, the ‘human capital’, the ‘social responsibility’ and the ‘children-centered’ were reviewed and used in order to flash light on the issue of child labour abuse in the study area. Child labour is not exhaustively studied in the country in general and in Wonchi district in particular. Findings from this study show that poverty, migration, child trafficking, parental unemployment, unfavorable educational system (i.e., absence of night schooling), and parental death and family breakdown are the major causes of child labour in the study areas. It also shows the impacts of child labour on the working children including the interface between child labour and education. It also puts impact on the holistic personality development of the child. It has physical, health and psychosocial impacts on the working children. Child labour and education are inversely related. Child labour affects the school enrollment and participation of children. High participation of children in school reduces the number of working children. Different people may have different perceptions towards child labour. Children may see child labour from different angle than employers and members of the society. Some children view ‘work’ as useful for their survival. Some others perceive it as something detrimental to their holistic development. Employers have different views and stressed that they employ children to help them meet their basic needs and shape their future. Members of the society perceive ‘child labour’ something ‘useful’ and ‘harmful’, and hold moderate attitude. The other most important finding of this study is the challenges working children face when they try to escape from labour exploitation. Some of these are poverty, inability to afford transportation cost, violent employers, intimidation by employers, etc. They also encounter physical, verbal and psychological abuses from employers, ‘parents’ or ‘relatives’, elder coworkers and customers. In short, this study ignites green light for further studies, and provide fertile ground for possible intervention policy makers on the problem of child labour abuse in the study area and the country at large.
The Case Of Wonchi District, Wonchi